Informal Caregivers in Pediatric and Adolescent Oncology in Chile: Unmet Supportive Care Needs and the Role of Oncology Health Navigators - Francisca Vezzani; Antonia Roberts; CABIESES VALDES, BALTICA BEATRIZ; CAMPAÑA, CARLA; Manuel A. Espinoza; OBACH KING, ALEXANDRA ALICE (SAGE Publications, 2026)
Informal caregivers of children and adolescents with cancer, predominantly women, frequently manage complex treatment and care demands with minimal support. This study explores the unmet supportive care needs of informal caregivers of children and adolescents with cancer, as well as their experiences and relationships with oncology health navigators, who have recently been incorporated into the Chilean public healthcare system. A qualitative multiple-case study was employed, with macro-regions (north, center, and south) defined as cases and caregivers as embedded units, selected to capture regional variability in carers’ experiences. Twenty-three in-depth interviews were conducted with female caregivers. Based on conventional content analysis, four unmet supportive care needs were identified: the need for humanized treatment, clear and timely information, adequate psychosocial support, and sufficient social protection. It was also observed that participants’ limited knowledge of the role of oncology health navigators in healthcare services limits the potential of these navigators to reduce inequities. These findings reveal substantial gaps in caregiver support, emphasizing the importance of enhancing oncology health navigator programs and integrating the role of civil society organizations within the care system. Integrating caregivers’ unmet supportive care needs in the design of pediatric oncology services, with a gender perspective, is essential to ensure a more equitable health system.